Distribution of Culicoides sonorensis (Diptera: Ceratopogonidae) in Nebraska, South Dakota, and North Dakota: Clarifying the Epidemiology of Bluetongue Disease in the Northern Great Plains Region of the United States - Schmidtmann, E. T. (2011)
The presence or absence of the biting midge Culicoides sonorensis Wirth & Jones (Diptera: Ceratopogonidae), a primary vector of bluetongue viruses (genus Orbivirus, family Reo viridae, BTV) in North America, was assessed on ranches and farms across the Northern Great Plains region of the United States, speciÞcally Nebraska, South Dakota, and North Dakota, as part of a 2-yr regional study of BTV exposure among cattle. Blacklight/suction trap samples totaling 280 2-night intervals were taken at 140 aquatic sites (potential larval habitat for C. sonorensis) on 82 livestock operations (ranches and farms) that span a south-to-north gradient of expected decreasing risk for exposure to BTV. In Nebraska, C. sonorensis populations were common and widespread, present at 15 of 18 operations. Of 32 operations sampled in South Dakota, seven of which were sampled in successive years, 18 were positive for C. sonorensis; 13 of 14 operations located west of the Missouri River were positive, whereas 13 of 18 operations east of the river were negative. Of 32 operations sampled in North Dakota, seven of which were sampled both years, 12 were positive for C. sonorensis. Six of eight operations located west and south of the Missouri River in North Dakota were positive, whereas 18 of 24 operations east and north of the river were negative for C. sonorensis. These data illustrate a well-deÞned pattern of C. sonorensis spatial distribution, with populations consistently present across Nebraska, western South Dakota, and western North Dakota; western South Dakota, and North Dakota encompass the Northwestern Plains Ecoregion where soils are nonglaciated and evaporation exceeds precipitation. In contrast, C. sonorensis populations were largely absent east of the Missouri River in South Dakota and North Dakota; this area comprises the Northwestern Glaciated Plains Ecoregion and Northern Glaciated Plains Ecoregion where surface soils reßect Wisconsinan glaciation and precipitation exceeds evaporation. In deÞning a well-demarcated pattern of population presence or absence on a regional scale, the data suggest that biogeographic factors regulate the distribution of C. sonorensis and in turn BTV exposure. These factors, ostensibly climate and soil type as they affect the suitability of larval habitat, may explain the absence ofC.sonorensis, hence limited risk for exposure to BTV, across the eastern Northern Plains, upper Midwest, and possibly Northeast, regions of the United States.